2018
DOI: 10.1371/journal.pone.0203987
|View full text |Cite
|
Sign up to set email alerts
|

User experience of controlling the DEKA Arm with EMG pattern recognition

Abstract: IntroductionA commercially available EMG Pattern Recognition (EMG-PR) control system was adapted to interface with the multi-degree of freedom (DOF) DEKA Arm.PurposeTo describe users’ experience of controlling the DEKA Arm using EMG-PR.MethodsSample: Twelve persons with upper limb amputation participated, 10 with transradial (TR), 2 with transhumeral (TH) level amputation. Ten were male, and 11 were users of a prosthesis at baselines. Design: This was a two-part study consisting of in-laboratory prosthetic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…It is possible that the weight of the prosthesis impacted EMG-PR users differentially. This finding is supported by data from our qualitative study in which users explained how the device weight led to fatigue and contributed to problems in consistency of controls operation [17]. However qualitative analyses did not provide insight into why EMG-PR users may have been less satisfied with grip and wrist display.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…It is possible that the weight of the prosthesis impacted EMG-PR users differentially. This finding is supported by data from our qualitative study in which users explained how the device weight led to fatigue and contributed to problems in consistency of controls operation [17]. However qualitative analyses did not provide insight into why EMG-PR users may have been less satisfied with grip and wrist display.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, there were no differences in usability ratings for TH amputees using EMG-PR or IMUs, but statistically significant differences in satisfaction items related to the full arm system, wires and cables, Batteries Subscale and internal battery life. Prior analyses reported that the EMG-PR system drained the internal battery quickly, and provides rich examples of user complaints about the external wires and cables [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, training daily provides new users with the best control algorithm given the EMG features collected on that day and our experience suggests that over time they will become more stereotyped and thus have improved control. From the start, our training requires less time than pattern recognition algorithms which can require 14-40 h of upfront, inlab training with experienced professionals (Resnik et al, 2017(Resnik et al, , 2018a.…”
Section: Failedmentioning
confidence: 99%
“…Sense -Infinite Biomedical Technologies; Myo Plus -Ottobock). Although pattern recognition algorithms enable successful real-time grasp classification (15)(16)(17) and allow for control of a prosthetic hand during real-world functional tasks (18)(19)(20)(21), users and therapists both report that extended periods of training are typically necessary to achieve stable performance (22,23). It is important to note that training to use a prosthesis involves multiple stages-including learning about the underlying functioning of the control system and how to generate the requisite control signals (conceptual training), learning to control a physical prosthesis (control training), and learning to use the prosthesis for completing functional tasks (functional training) (24).…”
mentioning
confidence: 99%